Exploring Jasmonates in the Hormonal Network of Drought and Salinity Responses - Riemann, Michael; Dhakarey, Rohit; Hazman, Mohamed; Miro, Berta; Kohli, Ajay; Nick, Peter (Frontiers in Plant Science, 2015)
Present and future food security is a critical issue compounded by the consequences of climate change on agriculture. Stress perception and signal transduction in plants causes changes in gene or protein expression which lead to metabolic and physiological responses. Phytohormones play a central role in the integration of different upstream signals into different adaptive outputs such as changes in the activity of ion-channels, protein modifications, protein degradation and gene expression. Phytohormone biosynthesis and signalling, and recently also phytohormone crosstalk have been investigated intensively, but the function of jasmonates under abiotic stress is still only partially understood. Although most aspects of jasmonate biosynthesis, crosstalk and signal transduction appear to be similar for biotic and abiotic stress, novel aspects have emerged that seem to be unique for the abiotic stress response. Here, we review the knowledge on the role of jasmonates under drought and salinity. The crosstalk of jasmonate biosynthesis and signal transduction pathways with those of abscisic acid (ABA) is particularly taken into account due to the well-established, central role of ABA under abiotic stress. Likewise, the accumulating evidence of crosstalk of jasmonate signalling with other phytohormones is considered as important element of an integrated phytohormonal response. Finally, protein post-translational modification (PTM), which can also occur without de novo transcription, is treated with respect to its implications for phytohormone biosynthesis, signalling and crosstalk. To breed climate-resilient crop varieties, integrated understanding of the molecular processes is required to modulate and tailor particular nodes of the network to positively affect stress tolerance.